Avaliação da sensibilidade dolorosa em idosos hipertensos: estudos de casos e controles - Rebelatto, Marcelo Nascimento (2015)
Background: Hypoalgesia related to hypertension has been described and studied by many authors over the last few decades, but little is known about how it behaves in the elderly. Therefore the aim of this study was to establish whether there are differences in pain sensitivity between hypertensive and normotensive older adults. For this, we selected seventy-two elderly of which 36 were normotensive and 36 were hypertensive and the pressure pain threshold (PPT) was assessed on seven points bilaterally in both groups by means of pressure algometry. Two-factor analysis of variance (ANOVA) group and gender was performed, and the effect size was calculated using Cohen s index. Results: The PPT values were higher in the group of hypertensive older adults compared to the normotensive ones; that difference was significant (P < 0.05) for the following points: right and left trochanters, left trapezium, left L3/L4 and left anterior tibialis muscle. The correlations exhibited by the PPTs were stronger in the group of hypertensive older adults; hypoalgesia was more generalized among the hypertensive adults compared to the normotensive ones. Gender did not influence that difference, although the magnitude of the difference was greater among males compared to females. Conclusion: Hypoalgesia, as assessed by means of PPT, exhibited a relationship with arterial hypertension in older adults. The influence of gender on hypoalgesia exhibited by hypertensive individuals is controversial.